In vitro secondary generation of cytotoxic T lymphocytes in mice with mumps virus and their mumps-specific cytotoxicity among paramyxoviruses. - Hosaka, Y (1986)
Murine cells (L929, MC57G, and P815 mastocytoma) defectively infected with the egg-adapted vaccine strain of mumps virus were found to be susceptible to cytotoxic T-lymphocyte (CTL)-mediated lysis. In vitro secondary, but not in vivo primary, generated CTL caused cytolysis of these targets in an H-2-restricted manner. UV-inactivated-mumps virus-coated murine cells were also found to be susceptible to CTL-mediated lysis. Comparisons of murine CTL-mediated lysis by three paramyxoviruses (mumps, Sendai, and Newcastle disease viruses) indicated that no cross-reactivity occurred. The CTL response with mumps virus exhibited specific unresponsiveness patterns, as influenced by the H-2 K/D regions of the mouse strains, that were partially different from those of Sendai virus and Newcastle disease virus.